Birinci Dünya Savaşı’nda Gazze Muharebeleri / The Battles of Gaza in World War I - Ağaoğlu, Sami (Journal of History Culture and Art Research, 2017)
Abstract According to Germany’s demand, Ottoman Empire opened Canal Front which is one of the most important front lines of WWI to pass the Suez Canal and attack Egypt. There were two massive attacks between Ottoman and British. The first clash occured in 1915 and second took place in 1916. Result of Ottoman forces struggle with the British troops, Ottoman Empire were defeated but then Ottoman Empire counter attacked. They tried to prevent British attacks in the campaigns of Sinai and Palestine. The paper deals with the First and the Second Battle of Gaza that repelled English forces, the third Gaza Battle and its result, Yildirim Army Group (or Thunderbolt Army Group) of the Ottoman Empire that was formed in order to prevent advance of attackers and siege and fall of Jerusalem. Therefore, subsequent failures of the campaign and retreating to the Anatolia started. The research paper was based on archival documents, primary&secondary sources and memoirs. Öz Osmanlı Devleti, Birinci Dünya Savaşı’nın önemli cephelerinden olan Kanal cephesini Almanların isteği doğrultusunda Süveyş kanalının geçmek ve Mısır’a taarruz etmek amacıyla açmıştı. Osmanlı Ordusunun I. Kanal Seferi ve II. Kanal Seferi başarısız olunca, karşı saldırıya geçen İngiliz birlikleri Sina ve Filistin cephesinde, Gazze muharebeleri ile durdurulmaya çalışılmıştır. Araştırmamızda, İngiliz birliklerinin püskürtüldüğü I. ve II. Gazze muharebeleri, Birüssebi ve Gazze’nin elden çıktığı III. Gazze muharebesi, Osmanlı Devleti’nin bu yenilgiyi durdurabilmek için kurduğu Yıldırım Orduları Gurup Komutanlığı ve Kudüs’ün elden çıkışı ele alınmıştır. Böylelikle birbiri ardına gelen yenilgiler zinciri ile Osmanlı Ordularının Anadolu’ya çekilişi arşiv belgeleri, birinci elden kaynaklar ve hatıratlardan yararlanılarak işlenmiştir.